PENYELESAIAN SENGKETA TUMPANG TINDIH SERTIFIKAT HAK ATAS TANAH SECARA NON LITIGASI OLEH KANTOR PERTANAHAN KABUPATEN KUPANG - Rizky Alexander Poy; Siti Ramlah Usman; Helsina Fransiska Pello; Yossie M. Y. Jacob (UNES Law Review, 2023)
The land is essentially the most basic need for everyone so that the presence of the State is to ensure that everyone can be legally protected by their land ownership rights. Many legal problems occur in obtaining recognition from the State of the legal status of one's land ownership. The purpose of this research is to analyze the settlement of disputes overlapping land rights certificates in Non litigation by the Land Office of Kupang Regency. This research method is qualitative, this research was conducted at the Land Office of Kupang Regency, East Nusa Tenggara Province. The population of this research is the Head of the Kupang Regency Land Office 1 person, the Head of Section at the Kupang Regency Land Office 3 people and the Community 2 people. The sample of this research uses a saturated sample technique, which will be the sample in this study are all members of the population. The result of this research is the effort to resolve the dispute over the overlapping certificate of land rights of the Land Office of Kupang Regency in mediation efforts between the two parties in accordance with the Operational Standards and Procedures (SOP) that have been established based on the Regulation of the Minister of Agrarian Affairs Number 21 of 2020 concerning Handling and Settlement of Land Cases, namely by Mediation by bringing both parties with the Head of the Land Office as mediator. While the legal consequences when the occurrence of multiple certificates will cause the certificate does not guarantee legal certainty. Because basically the ownership status of one plot of land there is only one ownership status. It can be concluded that the certificate is strong evidence as long as the other party does not prove otherwise.